Analisis Peningkatan Keterampilan Berpikir Kritis Peserta Didik pada Materi Suhu dan Kalor - Wifa Alifatun Nisa; Muhammad Minan Chusni (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study aims to analyze students' critical thinking skills on emperature and heat material. This research used a quantitative approach with a descriptive method. The subjects were eleventh-grade students. The instrument used was an essay test based on Ennis’ critical thinking indicators, including elementary clarification, basic support, inference, advanced clarification, and strategy and tactics. Supporting data were obtained through observation and interviews. The results showed that students' critical thinking skills were still in the low category with an average score of 31.06. The highest achievement was found in elementary clarification, while the lowest was in inference and strategy and tactics. Therefore, students' critical thinking skills on temperature and heat material still need to be improved through learning that encourages higher-order thinking activities.